Solar drying of Butea monosperma (keshuda) flowers for herbal colour - Chavda, Prof. Tilak Vithalbhai (Indian Journal of Agroforestry, 2022)
The dryer was evaluated with and without load condition for Keshuda flowers (Butea monosperma) in winter and summer seasons and its economic evaluation was calculated. The readings of temperature – relative humidity at different locations and solar insolation taken on October to December (Winter season) and March to May (Summer season). During winter and summer season, the maximum temperature inside the solar tunnel dryer was 50-54°C and 51-59°C at 2 p.m. and at the same time solar intensity was around 850 W/m² and 960 W/m², ambient temperature was around 34°C and 38°C, and inside relative humidity was around 30% and 12% during no load test respectively. It is observed that the drying time of Keshuda flowers required 15 h inside the dryer as compared to 27 h in open sun drying method in winter. In summer, Keshuda flowers required 13 h inside the dryer as compared to 21 h in open sun drying method to reduce moisture content up to 10% (w.b.) inside the dryer and in open sun drying. Collection efficiency and pick up efficiency of solar tunnel dryer was found as 59.37% and 16.62% respectively whereas system drying efficiency varies between 12.31-21.20%. The average 33.00% saving in time was observed using solar tunnel dryer over open sun drying method. The Net Present Worth, Payback period and Benefit-Cost ratio was found as ₹ 10,52,119.00, 6.2 months and 2.67 respectively.